2003
DOI: 10.1017/s0952836902003242
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic and terrestrial locomotor speeds of amphibious sea‐snakes (Serpentes, Laticaudidae)

Abstract: Amphibious animals may be subject to strong but conflicting selective pressures to enhance locomotor performance both on land and in the water. Biomechanical models suggest that in snakes, adaptations to swimming (e.g. reduction of ventral plates, flattening of tail) will reduce their ability to move on land. The locomotor speeds of six taxa of amphibious (laticaudid) sea‐snakes, plus one entirely marine (hydrophiid) species were measured. Because the relative dependence on aquatic vs terrestrial habitats vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 23 publications
6
58
0
Order By: Relevance
“…Despite the tractability and simplicity of elongate fish as a model system in which to address this question, few studies have directly compared axial-only locomotion in aquatic versus terrestrial environments. In addition, most such studies have considered only undulation frequency and/or overall animal velocity (Jayne, 1986;Shine and Shetty, 2001;Shine et al, 2003), with a much smaller subset encompassing other kinematic variables (Gillis, 1998;Ellerby et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Despite the tractability and simplicity of elongate fish as a model system in which to address this question, few studies have directly compared axial-only locomotion in aquatic versus terrestrial environments. In addition, most such studies have considered only undulation frequency and/or overall animal velocity (Jayne, 1986;Shine and Shetty, 2001;Shine et al, 2003), with a much smaller subset encompassing other kinematic variables (Gillis, 1998;Ellerby et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In such cases, natural selection will result in some compromise, i.e., an intermediate phenotype that can perform both tasks reasonably, but never as optimally as a specialised phenotype. Because such trade-offs may be widespread, information on phenotypic traits under such conflicting selective forces may provide general insights into the nature of adaptive compromises (Shine et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In snakes, including sea kraits and other sea snake species, swimming speed increases with an increasing size of individuals (Jayne 1985, Shine and Shetty 2001, Shine et al 2003. Studies of common garter snakes also revealed that a higher maximum crawling speed is associated with an increasing body mass (Heckrotte 1967).…”
Section: Discussionmentioning
confidence: 99%
“…But Shine et al (2003) also proposed that too little is known about the relative significance of the two types of measures in laticaudine locomotion. Thus, we included both measures of speed in this study.…”
Section: Locomotor Performancementioning
confidence: 99%
See 1 more Smart Citation